Investigation on Sensing Performance of Highly Doped Sb/SnO2 - Zhifu Feng; Andrea Gaiardo; Matteo Valt; Barbara Fabbri; Davide Casotti; Soufiane Krik; Lia Vanzetti; Michele Della Ciana; Simona Fioravanti; Stefano Caramori; Alberto Rota; Vincenzo Guidi (Sensors, 2022)
Tin dioxide (SnO2) is the most-used semiconductor for gas sensing applications. However, lack of selectivity and humidity influence limit its potential usage. Antimony (Sb) doped SnO2 showed unique electrical and chemical properties, since the introduction of Sb ions leads to the creation of a new shallow band level and of oxygen vacancies acting as donors in SnO2. Although low-doped SnO2:Sb demonstrated an improvement of the sensing performance compared to pure SnO2, there is a lack of investigation on this material. To fill this gap, we focused this work on the study of gas sensing properties of highly doped SnO2:Sb. Morphology, crystal structure and elemental composition were characterized, highlighting that Sb doping hinders SnO2 grain growth and decreases crystallinity slightly, while lattice parameters expand after the introduction of Sb ions into the SnO2 crystal. XRF and EDS confirmed the high purity of the SnO2:Sb powders, and XPS highlighted a higher Sb concentration compared to XRF and EDS results, due to a partial Sb segregation on superficial layers of Sb/SnO2. Then, the samples were exposed to different gases, highlighting a high selectivity to NO2 with a good sensitivity and a limited influence of humidity. Lastly, an interpretation of the sensing mechanism vs. NO2 was proposed.